Microsoft Visual Basic .NET : - Vicarel, Donald (Thomson Course Technology, 2004)
This book is designed to be used with the third education of programming logic and design by Joyce Farrell. It provides the opportunity for those who want to learn the fundamentals of programming and also get a taste of an actual programming language and it provides hands-on activitiesfor beginning progarmmer as they assimilate the concept presented in programming Logic and Design